2004
DOI: 10.1109/jsen.2004.828387
|View full text |Cite
|
Sign up to set email alerts
|

Detection of GB and DMMP Vapors by Love Wave Acoustic Sensors Using Strong Acidic Fluoride Polymers

Abstract: In this paper, we present a comparative study of GB and DMMP vapor detection using Love wave devices. Acoustic sensors are optimized versus the mass loading effect according to theoretical results, and a specific sensitive coating based on polysiloxane polymer is used to ensure selectivity. Experimental results allow us to compare the interactions between the coating and both gases. An estimation of the diffusion coefficient of each gas (GB and DMMP) was performed and we linked the dynamic of the responses wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 9 publications
2
45
0
Order By: Relevance
“…6,7 Organophosphates are found as major components in chemical warfare agents such as tabun ͑GA͒, sarin ͑GB͒, and VX. 8 Recently, possibly due to concern about possible terrorist attacks, a number of reports have appeared on the detection of the organophosphonate DMMP using a variety of chemical sensor platforms: metal oxide sensors, 9,10 carbon nanotube sensors, 11,12 SAW sensors, 13 and microcantilever sensors. 14,15 While some of the required features for an electronic nose are satisfied according to these reports, most of them do not satisfy all the requirements ͓in particular, high sensitivity at low parts-per-trillion ͑ppt͒ concentrations, detection in several seconds, and reversible within a few minutes͔ simultaneously.…”
mentioning
confidence: 99%
“…6,7 Organophosphates are found as major components in chemical warfare agents such as tabun ͑GA͒, sarin ͑GB͒, and VX. 8 Recently, possibly due to concern about possible terrorist attacks, a number of reports have appeared on the detection of the organophosphonate DMMP using a variety of chemical sensor platforms: metal oxide sensors, 9,10 carbon nanotube sensors, 11,12 SAW sensors, 13 and microcantilever sensors. 14,15 While some of the required features for an electronic nose are satisfied according to these reports, most of them do not satisfy all the requirements ͓in particular, high sensitivity at low parts-per-trillion ͑ppt͒ concentrations, detection in several seconds, and reversible within a few minutes͔ simultaneously.…”
mentioning
confidence: 99%
“…Copyright 2004 American Chemical Society. Reprinted in part with permission from reference [19]. Copyright 2004 IEEE. ponse after exposure to DMMP.…”
Section: Polymersmentioning
confidence: 99%
“…In general, the authors found that polymers with phenol hydroxyl groups performed better than those containing fluorinated aliphatic hydroxyl groups. Zimmerman et al [19] used a Love wave acoustic sensor coated with a strong acidic fluoride polymer (Fig. 2), observing sub-ppm detection limits for the nerve agent, sarin.…”
Section: Polymersmentioning
confidence: 99%
“…Dimethyl-methyl-phosphonate (DMMP) is a typical simulant of Sarin that many researchers use in Sarin gas-related experiments. Various DMMP gas detection methods have been developed, including methods using semiconducting metal oxide (SMO) sensors [3,4], surface acoustic wave sensors [5][6][7][8][9], and micro-cantilever sensors [10,11]. Of the aforementioned sensors, SMO sensors have already been commercialized owing to their advantageously high response and short response time; however, they require a high operation temperature, preventing their widespread use.…”
Section: Introductionmentioning
confidence: 99%